Characterisation of lung function trajectories and associated early-life predictors in an Australian birth cohort study. Issue 1 (21st March 2022) - Sanna, Francesca; Locatelli, Francesca; Sly, Peter D.; White, Elisha; Blake, David; Heyworth, Jane; Hall, Graham L.; Foong, Rachel E.
Background: There is growing evidence that lung function in early-life predicts later lung function. Adverse events over the lifespan might influence an individual's lung function trajectory, resulting in poor respiratory health. The aim of this study is to identify early-life risk factors and their impact on lung function trajectories to prevent long-term lung impairments. Methods: Our study included participants from the Raine Study, a prospective pregnancy cohort, with at least two spirometry measurements. Lung function trajectories from the 6- to 22-year follow-ups were characterised using finite mixture modelling. Multinomial logistic regression analyses were used to evaluate the association between early-life predictors and lung function trajectories. Main results: A total of 1512 participants (768 males, 744 females), representing 53% of the whole cohort, were included in this analysis. Four lung function trajectories of forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC (z-scores) were identified. FEV1 and FVC trajectories were categorised as: "very low", "low", "average" and "above average", respectively. Based on their shape, lung function trajectories of FEV1 /FVC were categorised as "very low", "low–average", "average–low" and "average". Asthma and maternal smoking were identified as risk factors for low lung function trajectories in this cohort, as well as early-life exposure to PM2.5Absorbance . Conclusions: Early-life risk factors may influence lung function trajectories over time. Nonetheless, identifying children with a high risk of having low lung function trajectories should be prioritised to prevent deficits in later life. Early-life risk factors may influence lung function trajectories over time. Nonetheless, identifying children with a high risk of having low lung function trajectories should be prioritised to prevent deficits in later life. https://bit.ly/3oYbgzr